2020
DOI: 10.21203/rs.3.rs-36957/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is health needs of chronic disease patients addressed during COVID-19 lockdown in India? A cross-sectional survey

Abstract: BackgroundThe novel corona virus disease (COVID-19) was declared as pandemic by World health organisation (WHO) on the 11th of March 2020. India was one among the countries in the world to declare the longest lock down across the nation in order to resist the spread of COVID-19. It was a challenge to assess the medical care of chronic disease patients during these lock down days.MethodologyWe adopted a cross sectional survey design to assess the health conditions and perceptions of patients with cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Another study among divorced or widowed and middle-aged female, adult patients with chronic diseases in Saudi Arabia showed that they were more vulnerable to have high levels of fear and health anxiety, which may lead to poor mental and physical health (Al-Rahimi et al, 2021). An online study in Kerala by Paul et al (2020) shows the challenges to assess the medical care of chronic disease patients during the lockdown days. They concluded that there is a strong need for health policy reformations in the field of the chronic diseases health.…”
Section: Introductionmentioning
confidence: 99%
“…Another study among divorced or widowed and middle-aged female, adult patients with chronic diseases in Saudi Arabia showed that they were more vulnerable to have high levels of fear and health anxiety, which may lead to poor mental and physical health (Al-Rahimi et al, 2021). An online study in Kerala by Paul et al (2020) shows the challenges to assess the medical care of chronic disease patients during the lockdown days. They concluded that there is a strong need for health policy reformations in the field of the chronic diseases health.…”
Section: Introductionmentioning
confidence: 99%